Are geopolymers more suitable than Portland cement to produce high volume recycled aggregates HPC? - Pacheco-Torgal, F. (2012)
The 70% minimum construction and demolition wastes-C&DW recycling rate set by the Revised Waste framework Directive No. 2008/98/EC to be enforced beyond 2020, will increase the need of effective recycling methods in a dramatic manner. So far, recycled aggregates (which constitute the majority of C&DW) are reused in low volume percentages for average compressive strength concretes and mostly as road sub-base and back-fill material which, in turn, constitutes a down-cycling option. Most investigations related to concrete made with recycled aggregates use aggregates produced in laboratory context which are not contaminated at all. It is then no surprise to find out that some investigations shows the potential to reuse as much as 100%, however, industrially produced recycled aggregates contain a certain level of impurities that can be deleterious for Portland cement concrete, thus making very difficult for the concrete industry to use such investigations unless uncontaminated recycled aggregates are used. This paper reviews current knowledge on concrete made with recycled aggregates, with a special focus on the crucial importance of impurities presence and how those aggregates are not suitable for the production of HPC. Also, the potential of geopolymers to produce HPC based on high volume recycled aggregates is discussed.